Enantioselective [1, 2]-Stevens rearrangement of thiosulfonates to construct dithio-substituted quaternary carbon centers. Issue 14 (21st March 2022) - Hu, Linfeng; Li, Jinzhao; Zhang, Yongyan; Feng, Xiaoming; Liu, Xiaohua
Abstract : An asymmetric [1, 2] Stevens rearrangement was realized via chiral guanidine and copper(i ) complexes. A series of novel chiral dithioketal derivatives were obtained with good yields (up to 90% yield) and enantioselectivities (up to 96 : 4 er). Abstract : An enantioselective [1, 2] Stevens rearrangement was realized by using chiral guanidine and copper(i ) complexes. Bis-sulfuration of α-diazocarbonyl compounds was developed through using thiosulfonates as the sulfenylating agent. It was undoubtedly an atom-economic process providing an efficient route to access novel chiral dithioketal derivatives, affording the corresponding products in good yields (up to 90% yield) and enantioselectivities (up to 96 : 4 er). A novel catalytic cycle was proposed to rationalize the reaction process and enantiocontrol.